Decision support system of the precedent type for managing the technological process of the second saturation of the sugar plant - Proskurka, Yevhen (My University, 2017)
Using decision support system of the precedent type for managing the technological process of the second saturation of the sugar plant is considered.
Keywords: topological analysis; precedent; топологічний аналіз; прецедент; топологический анализ; кафедра автоматизації та комп'ютерних технологій систем управління ім. проф. А.П. Ладанюка